Infiltrated Sr0.9Y0.1CoO2.5+δ nanoparticles as a cathode material for solid oxide fuel cells operated at 450–650 °C. (29th November 2019) - Si, Fengzhan; Shao, Lin; Kang, Xiaomin; Qin, Changyong; Huang, Kevin; Fu, Xianzhu; Luo, Jingli
Abstract: Catalytically active cathode materials are highly desirable for the development of low-temperature solid oxide fuel cells (LT-SOFCs). In the present study, we report the performance of a high-loading Sr0.9 Y0.1 CoO2.5+δ (SYC10) nanoparticles (NPs) as a catalytic cathode infiltrated in Ce0.8 Gd0.2 O2-δ (GDC) backbones for LT-SOFCs and the use of a low-loading SYC10 NPs as a catalyst for promoting the performance of a commercial cathode. The loading and calcination temperature of SYC10 NPs were systematically optimized to achieve the lowest area-specific polarization resistance at ≤650 °C. A significant reduction in polarization resistance of commercial LSCF cathode by SYC NPs has also been demonstrated at 650 °C. Highlights: SYC and the infiltration method have been chosen for high performance ITSOFC-cathode. Loading of SYC and sintering temperature have been optimized to 30 wt % and 350 °C. The optimum EIS performance tested at 500 °C is 0.733 Ω⋅cm 2 with the Ea 0.751 eV. Preeminent improvement has been found in the symmetrical LSCF/GDC/LSCF cell.